Analisis Yuridis Terhadap Gugatan Sita Jaminan Akibat Wanprestasi Pada Perjanjian Sewa Menyewa Mobil Berdasarkan Putusan Nomor 128/Pdt.G/2012/PN.DPK - Tambok Julius; Muhammad Farhan Bakhtiar; Nabilah Puspitarini; Achmad Hanif Avicenna; Sekar Marchayu Setiawan; Rheyna Wisnu Puteri (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
There are various types of agreements made by the community as written or oral guarantees for the transactions carried out. However, in leasing agreements, there are often problems of default on the rights and obligations between the parties that bring great losses to one of the parties, so many of the aggrieved parties sue for security seizure. The problem raised in the case analysis of decision number 128/Pdt.G/2012/PN.DPK is regarding the implementation of bail confiscation due to default in the agreement regarding the lease of a car that occurred and the settlement of the case from the bail confiscation of the default lawsuit in the lease agreement. The research method used is a normative juridical approach based on literature data from books, journals, and articles related to default accompanied by confiscation of collateral, which will be analyzed with a qualitative method. Based on the results of the analysis, it can be concluded that the implementation of security confiscation is one part of the rental agreement, so parties who have violated the agreement even though there is no written guarantee will be subject to sanctions. Thus, there is a need for understanding policies that emphasize rental transactions and provide awareness for related parties.